Between Jokes and Crime: A Legal Perspective on Catcalling in Public Spaces - Nur Rahmawaty Idrus; Askari Razak; Syamsul Alam (HORIZON PUBLIC LEGAL STUDIES, 2025)
This study aims to analyze the legal provisions for verbal harassment (catcalling) as a form of sexual harassment in public spaces and to examine the urgency of legal protection for victims in Indonesia. This study uses a normative legal research method with an emphasis on the study of applicable legal norms, principles, and principles, through a literature review covering primary, secondary, and tertiary legal materials, which are then analyzed qualitatively to find a match between the construction of norms and the reality of victim protection. The renewal of this study lies in the emphasis on strengthening the victim's perspective in reading the phenomenon of catcalling as a violation of human dignity and the right to feel safe in public spaces, while also testing the effectiveness of existing legal regulations in responding to contemporary social dynamics. The results of this study indicate that catcalling is a form of verbal sexual harassment that has real psychological and social impacts, and has received stronger legal recognition, although in practice it still faces obstacles in terms of proof, the capacity of officials, and cultural normalization in society. The conclusion of this study confirms that legal protection for victims is not yet fully optimal and requires strengthened implementation, consistent law enforcement, and a victim-sensitive approach.  This study recommends consistent law enforcement with a victim-centered approach, along with public education, increased collective awareness of the need to reject catcalling, and further studies on the effectiveness of its implementation in practice.